Perbedaan Tingkat Kecacatan Klien Kusta yang Aktif dan Tidak Aktif Mengikuti Kegiatan Kelompok Perawatan Diri (KPD) di Kabupaten Jember (The Difference in Impairment Level of Leprosy Clients who were Active and Inactive participating Self Care Group ( S - Frandita Eldiansyah; Wantiyah Wantiyah; Siswoyo Siswoyo (UPT Percetakan dan Penerbitan Universitas Jember, 2016)
Leprosy is an infectious disease caused by Mycobacterium leprae due to problems quite complex involve physical, psychological, social, economic, cultural, and spiritual problems. Physical problems such as impairment experienced by clients leprosy generally occur in the feet, hands, and eyes. Self-care group is a group of leprosy patients who come together to support each other primarily in prevention and reduction disabilities, also to find solutions for problems related to leprosy. The aim of this research was to analyze the difference in impairment levels of leprosy clients who were active and inactive participating Self Care Group (SCG) activities in Jember. This research used historical cohort study. The sampling collection technique used was total sampling involving 44 individuals, divided into 23 active leprosy clients and 21 inactive leprosy clients who participate SCG. Data analysis used Mann Whitney U-test with the significance level of 95% (α = 0.05). The research result showed that the average value of the active leprosy clients in impairment degree was 0.83 while the impairment degree of the inactive leprosy clients was 2.57. Data analysis showed that there was significant difference in impairment levels of leprosy clients who were active and inactive in participate Self Care Group (SCG) activities in Jember (p value 0.042, α = 0.05). Nurses are expected to create new innovations in the implementation of the SCG to increase participation of leprosy client's in the activities of the SCG then the impairment of leprosy client can be prevented and treated. Keywords: Leprosy, Impairment levels, Self Care Group (SCG)